Cinema demand in Germany - Ralf Dewenter; Michael Westermann (Universität Duisburg-Essen, Fachbereich Wirtschaftswissenschaften, 2003)
In the present paper we examine the German cinema market using time series data of 49 years. Applying estimation techniques such as OLS, 2SLS and SUR, we identify interrelations between the number of screens, the average real prices and the demand for movies per inhabitant. Furthermore, we test for the long run relationship and evaluate the elasticities of demand with respect to real price and income. Moreover, we analyse if cinema can be defined as an addictive good which can be explained with a myopic habit or rational addiction approach.
Keywords: C22; C32; L82; 330; cinema; demand; supply; habit formation; cointegration analysis; Seemingly Unrelated Regression; Kinowirtschaft; Nachfrage; Freizeitverhalten; Konsumentenverhalten; Schätzung; Deutschland